2017
DOI: 10.1111/tbj.12981
|View full text |Cite
|
Sign up to set email alerts
|

Impact of 2013 ASCO/CAP HER2 reporting guidelines in breast cancer: An assessment study from Indian oncology centre that primarily performs HER2 IHC testing with special emphasis on IHC equivocal category

Abstract: The ASCO/CAP guidelines for HER2 reporting in breast cancer published in 2007 and were updated in 2013 to assure that the right patient receives the targeted therapy. The updated guidelines have lowered the threshold for HER2 positivity criteria and altered the equivocal category for both IHC and FISH. This first study from India addresses the impact of these updated guidelines in the various reporting categories at a tertiary care centre. We compared the trend of HER2 IHC reporting 1 year before (Period A) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Total 16 studies [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were reviewed; of these there were 20 estimates, which has been summarized in web Table 1. This table highlights frequency and percentage of various HER2 reporting categories by FISH and IHC method according to both 2007 and 2013 guidelines.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Total 16 studies [11,[13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] were reviewed; of these there were 20 estimates, which has been summarized in web Table 1. This table highlights frequency and percentage of various HER2 reporting categories by FISH and IHC method according to both 2007 and 2013 guidelines.…”
Section: Resultsmentioning
confidence: 99%
“…The results are shown in Table 3a and b. In IHC category, data of 3 studies [23][24][25] were pooled with effective total sample size was 3056 (cases reported by 2007 guidelines) and 1554 (cases reported by 2013 guidelines). The increase in the equivocal category was from 23.7 to 26.7 % (P value: 0.025) while the increase in the positive category was from 12.9 to 15.8 % (P value: 0.0088), [ Table 3a].…”
Section: Resultsmentioning
confidence: 99%
“…HER2 positivity was defined as an immunohistochemical score of 3+ or a 2+ fluorescence in situ hybridization (FISH)-amplified as per the UK guidelines. 10 If the HER2 immunohistochemical score was 1+ or a 2+ score nonamplified on FISH, this was regarded as HER2-low breast cancer. 11 Detailed pathological review of the residual invasive carcinoma to assess for evidence of pathological response was undertaken.…”
Section: A T a C O L L E C T I O Nmentioning
confidence: 99%